Problem-goal principles of strategic planning of the regional education system development - Sychenko, Viktor; Khytko, Maiya (Public Administration and Regional Development, 2020)
The article examines the need and features of strategic planning of educational development at the regional level using existing problems as a basis for goal-setting management activities. Based on a systematic analysis and separation of common and special in the trends of educational development at the level of the country and the region, the basic problems of strategic planning and management are determined. At the national level, the basis of strategic planning for the development of education is the development of a new goal for the development of Ukrainian education based on the values of a democratic society, personal development, orientation to the European educational space. The generalized analysis of development of regional system of education on an example of the Dnepropetrovsk area with an exit on statement of the strategic purposes of its reforming is carried out. The problems of strategizing education management at the regional level and the need for related innovations in the regulatory and organizational sphere are emphasized. In order for the regional strategy in the field of education to provide access to quality education, take into account the requirements of socio-economic development of the region, it is extremely important to develop a purposeful regional program of innovative development of education. The most important in its development and implementation is to achieve real interaction of factors: political, social, economic, cultural and, in fact, educational. Based on the study, proposals are made to improve the strategic planning of the main components of the regional education system. The strategic priority of the educational strategy is the formation of a regional community that is constantly learning, while mastering democratic values, developing civil society, and affirming human-centeredness in education. An integrated strategy for innovation is needed in all spheres of education, as well as in other spheres of life in the region.